2015
DOI: 10.3109/00952990.2015.1094478
|View full text |Cite
|
Sign up to set email alerts
|

Integrating intervention for substance use disorder in a healthcare setting: practice and outcomes in New York City STD clinics

Abstract: Delivery of SUD services in a public health setting represents a significant policy and practice change and benefits many individuals whose SUDs might otherwise be overlooked. Intervention services for substance use disorder were integrated and highly utilized in the STD setting. Further research needs to focus on the long-term impact of SUD interventions in the STD setting, their cost effectiveness, and the extent they are financially sustainable under the new healthcare law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Pilot projects have demonstrated the feasibility and benefit of implementing substance use disorder interventions in STD clinics ( 9 , 10 ). STD programs should consider partnering with substance use disorder prevention and treatment programs and other organizations that provide services to persons who use drugs in the local community.…”
Section: Discussionmentioning
confidence: 99%
“…Pilot projects have demonstrated the feasibility and benefit of implementing substance use disorder interventions in STD clinics ( 9 , 10 ). STD programs should consider partnering with substance use disorder prevention and treatment programs and other organizations that provide services to persons who use drugs in the local community.…”
Section: Discussionmentioning
confidence: 99%
“…Although this pilot cannot speak to base rates of unassisted treatment entry in usual care, such rates are likely to be very low in a 1-month time span because STD clinic patients are not expressly seeking SUD treatment. A screening, brief intervention, and referral to treatment (SBIRT) program in New York City STD clinics found that 19% of patients referred to SUD treatment were eventually admitted to a treatment program, although only 7% did so within 30 days (Yu et al, 2016). Findings from the current pilot suggest that high rates of treatment entry can be achieved fairly quickly with SUD-focused patient navigation services.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research suggests that screening can effectively identify STD clinic patients with substance use problems, and supports the feasibility of providing interventions for substance use in the STD clinic setting (Appel et al, 2006; 2015; Lane et al, 2008; Yu et al, 2008). Moreover, there is emerging evidence that providing substance use interventions in STD clinic settings is associated with improved outcomes, including reduced incidence of STD infection detected at subsequent clinic visits (Rogers et al, 2015; Yu et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Screening-Brief Intervention-Referral to Treatment (SBIRT) programs, in which a substance use screening instrument is completed by all individuals receiving a service (i.e., all patients admitted to an Emergency Room or receiving primary care services at a hospital), have proven efficacy in identifying such individuals and reducing their substance use, even in instances where only the Brief Intervention component is used [5053]. SBIRT interventions have also been used in STD clinics and shown efficacy in reducing rates of STD infections [54,55]. In Argentina, however, where psychoanalysis remains the cornerstone of mental health treatment [56], these study findings also highlight the need for briefer, evidence-based treatments for substance use that may be more accessible to the general population.…”
Section: Discussionmentioning
confidence: 99%